A citation analysis of the Philippine Law Journal on foreign and international law sources (2000-2012) towards a collection-related library approach of the University of the Philippines Law Library - Sandoval, Eunice S.; Aguirre, Vyva Victoria M. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2013)
A law librarian should be able to provide the most effective materials to answer user needs. In a time where library budgets are getting smaller and library materials are getting more expensive, a law librarian should have a collection-oriented library approach to quantitatively assess the strength of his/her law library collection. One of the methods of this approach is citation analysis.
Citation analysis uses citations found from published sources, such as journals, to determine which materials are frequently cited by or referred to by UP Law Library users. It is a method that could give insight on how to build an effective collection-oriented law library collection and to determine where the users frequently get their resources. The source of citations of this study is articles citing foreign and international law sources from the Philippine Law Journal (PLJ) from 2000 to 2012. The gathered data were analyzed through descriptive statistics. Encoding and analysis of data were done through the use of Microsoft Excel, a spreadsheet software and SPSS Statistics, a statistical analysis program.
The study yielded 4,335 citations from 218 articles from the period of 2000 to 2012. The major findings of the study are the following: (1) the fields of Philippine Law that cited the most foreign and international law sources were: International Law with 1,118 citations (25.79%); Constitutional Law with 502 citations (11.58%); Intellectual Property Law with 310 citations (7.15%), and Family Law with 264 citations (6.09%); (2) the most predominant countries of publication were: United States with 3,062 citations (72.80%); United Kingdom with 585 citations (13.90%); Netherlands with 157 citations (3.70%), and Germany with 118 citations (2.80%); (3) the most predominantly used language was the English language with 4,239 citations (97.80%); (4) the most predominantly used formats were: Journal articles with 2,051 citations (47.30%); books with 1,316 citations (30.40%), and book articles with 427 citations (9.90%); (5) the mean age of materials cited was 15.63 years, and the mode age was 2 years, which means that the UP College of Law researchers have a need for current and updated legal information; (6) the most cited book titles were Principles of Public International Law by Ian Brownlie and The Least Dangerous Branch The Supreme Court at the Bar of Politics by Alexander M. Bickel with 12 citations each (.70%); (7) the most cited journal titles were the Harvard Law Review with 131 citations (6.10% of the total number of journal citations) followed by the Yale Law Journal with 48 citations (2.20%); (8) the most cited article title was The Right to Privacy by Samuel Warren and Louis Brandeis with 8 citations (.30%), followed by International Covenant on Economic, Social and Cultural Rights treaty with 7 citations (.20%); and (9) the most cited author was the United Nations with 86 citations (2%).
In the 4,335 citations gathered from the PLJ only 1,248 sources (28.30%) are available in the UP Law Library collection. In essence, the UP Law Library collection still needs to be improved and developed to satisfy the needs of its user community.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Philippine Law Journal; University of the Philippines (Diliman) Law Library; Bibliographical citations; Law -- Periodicals